1994
DOI: 10.1177/001789699405300305
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the mass media on public images of mental illness: media content and audience belief

Abstract: An analysis of media content in April 1993 found that two-thirds of items dealing with mental health issues forged a link between mental illness and violence. Using some of this material, the impact on the beliefs of an audience sample was explored. Six general groups and one user group took part in the study. Two-fifths of the general sample believed mental illness to be associated with violence and gave the media as their source. While some respondents with personal knowledge of mental illness, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 11 publications
5
99
0
Order By: Relevance
“…41,42 In addition, these stigmatizing attitudes, more predominantly with schizophrenia, have been linked to media influence. 43,44 Knowing this, the intervention began with a stereotypical video depicting a preview for a horror movie titled "Schizo." The clip ends with a man having tea with a friend and explains that he has schizophrenia and that there is nothing scary about him.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In addition, these stigmatizing attitudes, more predominantly with schizophrenia, have been linked to media influence. 43,44 Knowing this, the intervention began with a stereotypical video depicting a preview for a horror movie titled "Schizo." The clip ends with a man having tea with a friend and explains that he has schizophrenia and that there is nothing scary about him.…”
Section: Discussionmentioning
confidence: 99%
“…The private sector swiftly exploited these concerns for more effective treatment, and the ever-rising cost of placement in private hospitals, rather than a sound evidence base, has been a major influence in the expansion of medium secure units in the NHS. Doubling their formal admissions, from 814 to 1629 a year between 1994/1995 and 2004/2005, the independent hospitals now take some 24% of court and prison disposals (405 out of 1664) compared with some 6% (123 out of 2111) in 1994/1995(Information Centre, 2006. Furthermore the special hospitals had fallen foul of deprivations common to most total institutions (for example, see Goffman, 1961).…”
Section: Rise Of Forensic Psychiatrymentioning
confidence: 99%
“…Lurid media reports of crimes by people with mental disorders have become a principal source of information by which the public form their views about mental illness (Philo et al, 1994). The same preoccupation has filtered into government policy; the proposed revision of mental health legislation sought to reassure that the new law would be 'safe, sound and supportive' (Department of Health, 1998).…”
Section: The Inexorable Rise Of 'Risk'mentioning
confidence: 99%
“…A UK Food Standards Agency consumer survey (5) and a European study (3) stated that the public identified the media (press) within its top two sources of information on food and healthy eating. Bubela and Caulfield's research (6) concluded that the media provides an accurate reflection of what is conveyed by the research community, whereas Henderson et al (7) and Philo et al (8) suggested that the media can be inaccurate. Stryker (9) stated that 'inaccuracies resulting from the decontextualised and sensationalised manner in which stories are reported are conceptually distinct from, and occur with greater frequency than, actual errors contained within the story'.…”
Section: Literature Reviewmentioning
confidence: 99%